2012
DOI: 10.1152/ajpregu.00440.2011
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of cardiopulmonary depressor reflex in nucleus ambiguus by electroacupuncture: roles of opioids and γ-aminobutyric acid

Abstract: Stimulation of cardiopulmonary receptors with phenylbiguanide (PBG) elicits depressor cardiovascular reflex responses, including decreases in blood pressure and heart rate mediated in part by the brain stem parasympathetic cardiac neurons in the nucleus ambiguus (NAmb). The present study examined NAmb neurotransmitter mechanisms underlying the influence of electroacupuncture (EA) on the PBG-induced hypotension and bradycardia. We hypothesized that somatic stimulation during EA modulates PBG responses through o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
61
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(66 citation statements)
references
References 43 publications
5
61
0
Order By: Relevance
“…Gabazine microinjection into the NAmb briefly decreased heart rate by an average of 10 beats per minute (bpm). These changes are similar to those observed by us and others investigating neurotransmitter action in these nuclei (15,25,41).…”
Section: Physiological Studiessupporting
confidence: 91%
See 4 more Smart Citations
“…Gabazine microinjection into the NAmb briefly decreased heart rate by an average of 10 beats per minute (bpm). These changes are similar to those observed by us and others investigating neurotransmitter action in these nuclei (15,25,41).…”
Section: Physiological Studiessupporting
confidence: 91%
“…EA at P5-P6 acupoints activates NAmb neurons in close proximity to enkephalinergic processes, implying that EA exerts at least part of its cardiovascular actions through this nucleus and that enkephalin participates in EA processing in this region (13). Furthermore, we observed that EA at the P5-P6 acupoints inhibited evoked neuronal discharge in the NAmb during vagal afferent fiber stimulation (41), an action that was attenuated by blockade of GABA A receptors with gabazine. GABA A receptor blockade in this region also reverses EA-related modulation of bradycardia responses elicited during stimulation of cardiopulmonary vagal afferent endings in cats by intravenous administration of PBG, a 5-HT 3 receptor agonist (41).…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations